Empowering Posyandu Cadres and Community Service Program Students in Postpartum Care Assistance in Gondomanyu Hamlet - Armelia, Farisa Izmi; Tabi’ina Alfi Rohmah; Zafira Nahdiatul Imamah; Raka Astu Priyambadha; Nopatra Aditya Pratama; Anissa Ragilia Putri; Akhmad Habib Nur Fauzi (Simfoni Ilmu Cindekia, 2025)
The community service program (KKN) was carried out through a collaboration between university students, Posyandu cadres in Gondomanyu Hamlet, and the midwife of Tanjungsari Village to provide support, care, nurturing, and assistance to postpartum mother particularly those who still strongly adhere to tarak or food taboos during the six weeks following childbirth. The aim of this program was to enhance the capacity of local health cadres in educating and supporting postpartum mothers, as well as to strengthen the synergy between academic institutions and the community in addressing locally rooted health issues. The methods used included needs assessment through interviews and observations, as well as direct assistance provided to 13 postpartum mothers. The results showed that the involvement of KKN students in Posyandu activities significantly improved the cadres' ability to provide education on newborn care, exclusive breastfeeding, and counseling related to tarak culture. This collaboration also increased community awareness about the importance of postpartum care and encouraged more informed health-related decision-making.